Identification of mutations in AP4S1/SPG52 through next generation sequencing in three families. (22nd July 2016) - Tessa, A.; Battini, R.; Rubegni, A.; Storti, E.; Marini, C.; Galatolo, D.; Pasquariello, R.; Santorelli, F. M.
Abstract : Background and purpose: The term hereditary spastic paraplegia (HSP) covers a spectrum of genetically heterogeneous disorders in which lower limb spasticity is the common clinical feature. Many patients with childhood‐onset HSP are mistakenly diagnosed with cerebral palsy (CP). Methods: A group of as yet molecularly undiagnosed HSP patients were analyzed using SpastoPlex, a customized target re‐sequencing panel able to investigate the coding regions of 72 genes linked to HSP, spastic ataxias or related motor diseases. Results: Our investigations identified loss‐of‐function mutations in AP4S1 /SPG52 in four children (three families) who had previously received a diagnosis of diplegic/quadriplegic CP. The patients presented spastic paraparesis, mild facial dysmorphisms, moderate‐to‐severe intellectual disability and severe speech delay. Two patients manifested febrile seizures and childhood‐onset focal seizures. In all the patients, brain magnetic resonance imaging (MRI) showed a peculiar hypoplastic posterior corpus callosum, often associated with ventriculomegaly, white matter loss and cerebral atrophy. Conclusion: Adaptor protein 4 (AP‐4) deficiency disorders should be suspected in children with spastic paraparesis, cognitive deficit and absent speech accompanied by suggestive MRI features. Seizures might be amongst the clinical manifestations of the syndrome.